Egg quality and coccidiosis infestation in three production systems for laying hens - Reza Vakili; Ahmad Salahshour; Ali Zanganeh (Acta Scientiarum. Animal Sciences, 2021)
A total of 240 white Shaver laying hens from 22 to 34 weeks of age were assigned to 3 treatments and 5 replications. The treatments included: i) Conventional (hens were kept in experimental building without access to outdoor area and fed with the conventional diet), ii) Semi-organic (hens were kept in experimental building with access to outdoor area and fed with the organic diet plus amino acids and vitamin-minerals supplement), and iii) Organic (hens were kept in experimental building with access to outdoor and fed with the organic diet). The results showed statistically significant differences in the feed intake, egg production, egg mass, egg weight, and change body weight(g) means among the treatments (p < 0.05). The hens kept in the organic treatment had fecal highest contain of oocytes coccidia (p < 0.05). The yolk color index and shell strength in the organic treatment significantly increased in comparison with that of other treatments (p < 0.05). The highest HDL was in the semi-organic and organic treatments (p < 0.05). The lowest egg yolk cholesterol concentration was found in hens kept in the semi-organic and organic treatments (p < 0.05). It is concluded that organic production system is useful for improving egg quality.